Costs and Use of Health Care in Patients With Celiac Disease: A Population-Based Longitudinal Study. (August 2020) - Mårild, Karl; Söderling, Jonas; Bozorg, Soran R.; Everhov, Åsa H.; Lebwohl, Benjamin; Green, Peter H.R.; Neovius, Martin; Ludvigsson, Jonas F.
Abstract : INTRODUCTION: Celiac disease (CD) affects 1% of the population. Its effect on healthcare cost, however, is barely understood. We estimated healthcare use and cost in CD, including their temporal relationship to diagnosis. METHODS: Through biopsy reports from Sweden's 28 pathology departments, we identified 40, 951 prevalent patients with CD (villous atrophy) as of January 1, 2015, and 15, 086 incident patients with CD diagnosed in 2008–2015, including 2, 663 who underwent a follow-up biopsy to document mucosal healing. Each patient was compared with age- and sex-matched general population comparators (n = 187, 542). Using nationwide health registers, we retrieved data on all inpatient and nonprimary outpatient care, prescribed diets, and drugs. RESULTS: Compared with comparators, healthcare costs in 2015 were, on average, 1, 075 (95% confidence interval, 864–1, 278) higher in prevalent patients with CD aged <18 years, 715 (632–803) in ages 18–64 years, and 1, 010 (799–1, 230) in ages ≥65 years. Half of all costs were attributed to 5% of the prevalent patients. Annual healthcare costs were 391 higher 5 years before diagnosis and increased until 1 year after diagnosis; costs then declined but remained 75% higher than those of comparators 5 years postdiagnosis (annual difference = 1, 044). Although hospitalizations, nonprimary outpatient visits, and medication use were all more common with CD, excess costs were largely unrelated to the prescription of gluten-free staples and follow-up visits for CD. Mucosal healing in CD did not reduce the healthcare costs. DISCUSSION: The use and costs of health care are increased in CD, not only before, but for years after diagnosis. Mucosal healing does not seem to lower the healthcare costs.